Comparitive Evaluation of Novel Desensitising Agents on Dentinal Tubule Occlusion-A Scanning Electron Microscopic Study (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: dentinal hypersensitivity; novamin; gluma; diode laser; pro-arginine; scanning electron microscope